Risk Factors for Skin Cancer in the Salud Delicias Area - Yanet Hernández Caballero; María del Carmen Pérez Cuesta; Leticia Rómulo Ávila; Yoenny Peña García (Revista Finlay)
Background: skin cancer has a high incidence, with an upward trend worldwide. These carcinomas are preventable both by lifestyle changes and by detecting lesions indicative of malignant transformation. Objective: to determine the risk factors for skin cancer in the population of office number 4 of the Delicias Health Area. Method: an epidemiological, observational, analytical study of cases and controls was carried out in the period 2017-2021. The study population consisted of 13 patients (case group) and 26 patients (control group), for a total of 39 cases included, all over 15 years of age. The variables were studied: age, sex, skin color, occupation, time of exposure to the sun, means of protection, contact with chemical substances. The information was obtained from the medical records and a questionnaire, it was analyzed through the percentage calculation, the Chi2 and the odd ratio. Results: participants older than 55 years (38.5 %), male sex (69.2 %) predominated. They had a higher risk of skin cancer: those with white skin color (Chi2: 3.3; OR: 6.4; p<0.05), occupation with sun exposure (Chi2: 4.4; OR: 5, 5 p<0.05), more than 3 years in the occupation (Chi2: 3.3; OR: 6.4; p<0.05), exposed after 11 a.m. (Chi2: 3.3; OR: 3.6 p<0.05), without use of protective means (Chi2: 7.8; OR: 14; p<0.05), contact with chemical products (Chi2: 7.4; OR: 8.8; p<0.05) and a family history of cancer (Chi2: 2.6; OR: 3; p<0.05). Conclusions: those over 55 years of age and men predominated, a statistical and causal association was demonstrated between skin cancer and the risk factors studied.